HUBUNGAN SANITASI LINGKUNGAN DAN HIGIENE PERSEORANGAN DENGAN KEJADIAN SKABIES DI RUTAN CABANG SIBUHUAN KABUPATEN PADANG LAWAS TAHUN 2013 - Asrul Hamonangan Pasaribu; nurmaini *; devi nuraini santi (Lingkungan dan Kesehatan Kerja, 2014)
ABSTRACT Scabies is known in Indonesia as gudik, kudis, buduk, kerak, penyakit ampera or gatal agogo or body louse. This diseases is transmitted from human being to the human being, from animals to human being, and conversely. The prevalence of scabies at the Puskesmas (primary health care) in Indonesia is 4,6% – 12,9% and scabies is on the third rank of 12 skin diseases. The prevalence of scabies is the higher in environment with the higher density and the poor sanitation. This research aims to study a correlation between environment sanitation and personal hygiene with the scabies incident at Rutan (detention center) branch of Sibuhuan, regency of Padang Lawas. The applied method in this research is analytic by corss sectional design. The population of this research is all of prisoners who live in Detention center branch of Sibuhuan. The sample is total population for 42 persons. The data is analyzed by univarian and bivarian with Chi – square test on significant level 95%. The results of study indicates that environment sanitation variable, i.e. the floor condition (p = 0,001) has a correlation to the scabies incident. The variable of ventilation, humidity, lighting and availability of pure water are not considered because fulfill requirement by the density of the detention center did not fulfill the health requirement. The personal hygiene variable, i.e. genital cleanness (p = 0,029) and clothes and towel cleanness (p = 0,014) has a correlation to the scabies incident. While the skin and hair cleanness variables (p = 0,286), the hand, foot and nail cleanness (p = 0,636) and the cleanness of bad and bad cover (p = 0,654) has not a correlation to the scabies incident. It is suggested the Management of Rutan (detention center) Branch of Sibuhuan Regency of Padang Lawas to regulate the density of the facility and improve the floor condition and to maintain the environment sanitation of the detention center to minimize the scabies. Keywords : Scabies, Environment Sanitation, Personal Hygiene